The Effect of Social Media and Smartphone Use on Mathematics Learning Interest among Students at SMP Negeri 2 Singingi - Intan Nurhakiki, Desti; Suripah; Istikomah, Endang; Indriati, Mefa; Wulandari, Happy (Universitas Islam Negeri Raden Intan Lampung, 2026)
The rapid expansion of digital technology has transformed students’ learning experiences, yet its influence on mathematics learning interest remains inconclusive because social media and smartphone use have often been examined separately. This study investigated the individual and simultaneous relationships between social media use, smartphone use, and mathematics learning interest among junior high school students. A quantitative ex post facto cross-sectional design was employed involving all 76 eighth-grade students at SMP Negeri 2 Singingi, Indonesia, using saturated sampling, while data were collected through three validated Likert-scale questionnaires and analyzed using multiple linear regression after the required statistical assumptions were satisfied. The findings revealed that both social media use and smartphone use were significant positive predictors of mathematics learning interest, and the regression model demonstrated a statistically significant overall fit. The results suggest that digital technology contributes positively to students’ affective engagement with mathematics when it is used purposefully to access educational content, facilitate learning interaction, and support independent study rather than merely for recreational activities. Unlike previous studies that predominantly investigated digital platforms or mobile devices separately or focused primarily on academic achievement, this study integrates both dimensions of students’ digital learning behaviour within a single analytical framework while positioning mathematics learning interest as the primary educational outcome. The findings contribute to the literature on digital mathematics education by providing empirical evidence from an Indonesian junior high school context and highlighting the importance of digital literacy, self-regulation, and pedagogically guided technology integration in promoting meaningful and sustainable mathematics learning.